Analisis kemampuan penalaran spasial dalam penyelesaian soal transformasi geometri - Astuti, Erni Puji; Handayani, Reza Septia; Ngulia, Karisma Nurul; Lestari, Dwi; Saktiyani, Debi; Pradana, Sintya Linggar (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2025)
Spatial reasoning ability significantly affects mathematics learning in the area of geometric transformations. However, students’ spatial reasoning ability is still underdeveloped. This study focused on analyzing students’ spatial reasoning ability while working on problems involving geometric transformations. Data were collected through a spatial reasoning ability test and personal interviews. The subjects were six grade XI students. The research design applied was descriptive qualitative. It was found that students with high spatial reasoning ability could mentally analyze and understand rotation patterns, envision objects moving in a clockwise direction, determine dilation and reflection of an object about a specific axis, and comprehend spatial changes and the position of objects and shapes in space. Students with moderate spatial reasoning ability could understand the rotation patterns and mentally picture the objects moving clockwise; however, they could not grasp the concept of object transformations correctly. Low spatial reasoning ability could not grasp the problem and visualize the rotation of the objects, resulting in an inability to determine the transformation of the object position. This also prevented the students from solving the transformation concept. This study has been able to identify specific aspects that need to be addressed in the geometric transformation topic. This research can help inform the design of more effective and innovative learning strategies.